The Association of Children's Blood Lead Levels and Prevalence of Stunting in Tin Mining Area in Indonesia - Rismarini Zarmawi; Budi Haryanto (Ubiquity Press, 2023)
Background: Metal mining and smelting activities are regarded as major sources of heavy metals such as lead, mercury, arsenic and cadmium in the environment and in humans living at the surrounding area. Among others, lead can enter and accumulate in the human body and be very influential in children's growth and development. Objective: This study aims to assess the association between children's blood lead levels and stunting in a mining area in Indonesia. Methods: A cross-sectional design was implemented by involving 193 children living in surrounding tin mining in Bangka Island, Indonesia. Venous blood was drawn and blood lead level was measured by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Stunting status was measured by anthropometry standing height and converted to sexand age-specific Z-scores based on World Health Organization (WHO) growth reference. Children's dietary intake was assessed using 24-hour dietary recall method. Statistics of chi-square test and multiple logistic regression were performed for the analyses. Findings: The geometric mean of Blood Lead Levels (BLLs) was 5.5 µg/dl (± 2.6 µg/dl; 95% CI: 5.1-5.9). The interquartile range of BLLs and height for age Z-score (HAZ) were 3.0 μg/dl and -1.5, respectively. The data revealed that 23.3% of children were stunted (HAZ < -2). The multiple logistic regression models suggest that elevated BLLs were an independent predictor of the stunting. The odds stunted blood lead concentration was elevated about 10times higher [adjusted odd ratio (AOR) = 9.75 (95% Confidence interval (CI): 3.1-30.7); p < 0.001] in comparison to the odds of normal BLLs. The BLLs of children at ages two to nine years were found associated with stunting after controlling of the mother›s education, residence and the intake of energy, protein, zinc, vitamin A, calcium and phosphorus. Conclusion: The study suggested that living in surrounding tin mining was dangerous for children›s health and their development.